First Report of Root Rot Caused by Pythium spiculum Affecting Cork Oaks at Donana Biological Reserve in Spain - De Vita, P.; Serrano, M. S.; Ramo, C.; Aponte, C.; Garcia, L. V.; Belbahri, L.; Sanchez, M. E. (PLANT DISEASE, 2013)
APSAPSThe following values have no corresponding Zotero field: pub-location: 3340 PILOT KNOB ROAD, ST PAUL, MN 55121 USA publisher: AMER PHYTOPATHOLOGICAL SOC
Keywords: Cork oak; Donana Biological Reserve; Pythium spiculum; Spain

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - Serrano, M. S.; Sanchez, M. E.; De Vita, P.; CARBONERO, M. D.; Trapero, A.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: decline; Holm oak; root rot; yellow lupine

Pathogenicity of Pythium spiculum and P-sterilum on feeder roots of Quercus rotundifolia - Jimenez, J. J.; Sanchez, J. E.; Romero, M. A.; Belbahri, L.; Trapero, A.; Lefort, F.; Sanchez, M. E. (PLANT PATHOLOGY, 2008)
APSAPSThe following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: pathogenic; Pythium spiculum; Pythium sterilum; Quercus ilex

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - Sanchez, M. E.; Andicoberry, S.; Trapero, A. (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
The following values have no corresponding Zotero field: publisher: Blackwell Verlag GmbH
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management - Garcia, F. P.; Sanchez, M. E.; Diaz, F. J. M.; Vega, A. R. D. (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.
The following values have no corresponding Zotero field: periodical: BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS issue: 90 pub-location: POSTBUS 220, 6700 AE WAGENINGEN, NETHERLANDS
Keywords: Dehesa; environmental econ; sustainable management